Power Eliminates the Influence of Body Posture on Facial Emotion Recognition. - Civile, Ciro; Obhi, Sukhvinder (Journal of Nonverbal Behavior, 2016)
The article offers information on a research on eliminating the influence of body posture on facial emotion recognition by power priming. Topics discussed include priming participants to low, high, or neutral power prior to their performance in a facial-emotion categorization task; congruence effect for compound checkerboard stimuli; and effect of congruence of facial and body emotions on low-power and neutral-power participants.